Neonatal BCG vaccination to prevent asthma: Results from the MIS BAIR randomized controlled trial - Laure F. Pittet; Emily Forbes; Susan Donath; Kate Francis; Kaya Gardiner; Katie L. Flanagan; Anne‐Louise Ponsonby; Roy M. Robins‐Browne; Frank Shann; Mike South; Peter Vuillermin; Dan Casalaz; et al. (2025)
Asthma has a significant impact worldwide, but prevention strategies remain limited. We aimed to evaluate the efficacy of neonatal BCG vaccination in preventing asthma by modulating early-life immunity. The Melbourne Infant Study: BCG for Allergy and Infection Reduction (MIS BAIR) was a phase 3 multicentre randomized controlled trial in Victoria, Australia. Infants were randomly assigned to receive the BCG-Denmark vaccine or no intervention within 10 days of birth. The incidence of asthma at 5 years of age was estimated using the International Study of Asthma and Allergies in Childhood questions. gov (NCT01906853). A total of 1272 infants were randomized. The adjusted incidence of asthma was 14.4% in the BCG group compared to 16.0% in the control group (adjusted risk difference [aRD] -1.7 percentage points; 95%CI -7.4, 3.9). Secondary outcomes, including severe asthma and use of preventer medication, showed similar trends, with an aRD of -3.9 (95%CI -7.7, 0.0), and -5.6 (95%CI -10.9, -0.4), respectively, favoring the BCG group. Among participants with one or both parents asthmatic, the rate of asthma was also lower in the BCG group (17.6%) compared with the control group (24.7%; aRD -7.2; 95%CI -15.9, 1.5), although a test for interaction was not significant (p = .07). While the point estimates suggested BCG vaccination might protect against asthma, the wide uncertainty around the estimates means further studies with larger sample sizes are needed to evaluate the long-term benefits of BCG vaccination beyond its primary indication.